Does cold-water immersion after strength training attenuate training adaptation? - Poppendieck, W.; Wegmann, M.; Hecksteden, A.; Darup, A.; Schimpchen, J.; Skorski, S.; Ferrauti, A.; Kellmann, M.; Pfeiffer, M.; Meyer, T. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Cold-water immersion is increasingly used by athletes to support performance recovery. Recently, however, indications have emerged suggesting that the regular use of cold-water immersion might be detrimental to strength training adaptation. Methods: In a randomized crossover design, 11 participants performed two 8-week training periods including 3 leg training sessions per week, separated by an 8-week "wash out" period. After each session, participants performed 10 minutes of either whole-body cold-water immersion (cooling) or passive sitting (control). Leg press 1-repetition maximum and countermovement jump performance were determined before (pre), after (post) and 3 weeks after (follow-up) both training periods. Before and after training periods, leg circumference and muscle thickness (vastus medialis) were measured. Results: No significant effects were found for strength or jump performance. Comparing training adaptations (pre vs post), small and negligible negative effects of cooling were found for 1-repetition maximum (g = 0.42; 95% confidence interval [CI], -0.42 to 1.26) and countermovement jump (g = 0.02; 95% CI, -0.82 to 0.86). Comparing pre versus follow-up, moderate negative effects of cooling were found for 1-repetition maximum (g = 0.71; 95% CI, -0.30 to 1.72) and countermovement jump (g = 0.64; 95% CI, -0.36 to 1.64). A significant condition × time effect (P = .01, F = 10.00) and a large negative effect of cooling (g = 1.20; 95% CI, -0.65 to 1.20) were observed for muscle thickness. Conclusions: The present investigation suggests small negative effects of regular cooling on strength training adaptations.